A fé como fator de resiliência no tratamento do câncer: uma análise do que pensam os profissionais da saúde sobre o papel da espiritualidade na recuperação dos pacientes - Bartolomei, Mônica (2008)
This work has as its objective studying the subject of resilience when referring to persons with great suffering, living traumatic situations and of loss, such as in the case of terminal illnesses. Thus, studies were developed to research in literature the understanding of faith as a factor of resilience in the treatment of cancer. In order to meet the criteria of scope and ethical pleading, the research based itself on the analysis of what the health professionals think on the role of spirituality in the recovery of patients. The proximity between the reality of the practice of certain professional categories and the studies which associate patients with cancer to resilience is patent. Churchmen, psychologists and medical doctors were interviewed so as to allow the theoretic referential to fit in, obtained through bibliographic research into professional experience, found in the field of research, and thus to conclude the work. In this way one can see the perfect attuning between the experience of churchmen when exploring the subjects of terminality, of faith and their relation to illness and the capacity to overcome by certain individuals. The aspect of faith as an element, pure and simple, for curing was widely examined, having received extremely varying contributions, from the total release from the illness, against all medical prognoses, to strongly pragmatic positions, which refuse to accept any influence whatsoever of faith in the course of the evolution of the facts. Principally, churchmen and psychologists are in agreement when approaching the meaning of the traumatic event and the stimulus of resilience, over which the influence of the cultural and religious roots of the patient are exerted, perfectly in line with the theoretic basis, proposing fighting adversity by building a feeling of coherence, which it its self makes suffering manageable